2016
DOI: 10.1039/c5en00222b
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity of dimercaptosuccinate-coated and un-functionalized magnetic iron oxide nanoparticles towards aquatic organisms

Abstract: Investigations on colloidal stability and ecotoxicological effects of DMSA-coated and uncoated IONP with Raphidocelis, Daphnia and Lemna.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 67 publications
0
17
0
Order By: Relevance
“…The average crystallite/grain size is estimated using the Debye–Scherrer formula: D = kλ / β cos θ , where D is the average crystal size, k is the Scherrer coefficient (0.9), λ is the X‐ray wavelength (= 1.54 Å), β is the full‐width half‐maximum intensity and θ is the diffraction angle . The estimated average crystallite size of Ag NPs is 11 nm calculated from the width of the [111] Bragg reflection.…”
Section: Resultsmentioning
confidence: 99%
“…The average crystallite/grain size is estimated using the Debye–Scherrer formula: D = kλ / β cos θ , where D is the average crystal size, k is the Scherrer coefficient (0.9), λ is the X‐ray wavelength (= 1.54 Å), β is the full‐width half‐maximum intensity and θ is the diffraction angle . The estimated average crystallite size of Ag NPs is 11 nm calculated from the width of the [111] Bragg reflection.…”
Section: Resultsmentioning
confidence: 99%
“…The results from the paper also suggested that toxicity can occur due to a decrease in colloidal stability, release of ions from the core material and formation of ROS, but more importantly they discussed how the negative charge carrier coatings of ASC and CIT-IONP seems to be of lesser importance of being tested in vivo in comparison to in vitro [ 145 ]. Along similar lines, when the toxicity of DMSA-coated and unfunctionalized MNPs (fresh and aged uncoated IONP) was tested on three aquatic organisms, namely green algae ( Raphidocelis subcapitata ), duckweed ( Lemna minor ) and water fleas ( Daphnia magna ), the results validated the green algae to be the most sensitive with an EC 50 of 0.86–2.27 μM at 72 h in comparison to daphnia which displayed minor effects iwith uncoated IONPs over a wide concentration range of 1.0 × 10 −6 to 100 mg/L [ 146 ]. Later in another study, the mechanistic role of these NPs was considered after they were provided orally to Drosophila (fruit fly) as a model organism.…”
Section: Mnp Toxicity In Vitro and In Vivomentioning
confidence: 99%
“…The literature contains some lab-scale toxicity assessment of novel adsorbents. [318][319][320][321][322][323][324][325][326] These data are derived for systems which do not mimic and capture the real lifecycle components and complexity of micro-and macro environments to which the SMART adsorbents can be exposed in real-world water treatment systems. They also do not account for how ecosystems downstream influence the final treated effluent discharge.…”
Section: Discussionmentioning
confidence: 99%